Fondaparinux Pre-, Peri-, and/or Postpartum for the Prophylaxis/Treatment of Venous Thromboembolism (FondaPPP). (3rd May 2021) - Dempfle, Carl-Erik; Koscielny, Jürgen; Lindhoff-Last, Edelgard; Linnemann, Birgit; Bux-Gewehr, Irene; Kappert, Günther; Scholz, Ute; Kropff, Stefan; Eberle, Sonja; Bramlage, Peter; Heinken, Andreas
We analyzed data for women who received fondaparinux for ≥7 days during pregnancy. The study retrospectively included women who received fondaparinux pre-, peri- and/or postpartum for ≥7 days for prophylaxis/venous thromboembolism (VTE) treatment at German specialist centers (2004-2010). Data on pregnancy, VTE risk factors, anticoagulant treatment, pregnancy outcome and adverse events were extracted from medical records. 120 women (mean age 31.5 years) were included. Among 84 women with prior pregnancies, 41.0% had ≥1 abortion. Anticoagulation was indicated for prophylaxis in 92.5% cases, including 82.5% women with an elevated VTE risk (82.8% thrombophilia, 34.2% VTE history). All women received low-molecular-weight heparin (LMWH) as first-line therapy; 3 also unfractionated heparin. Treatment changed to fondaparinux, due to heparin allergy (41.7%) or heparin-induced thrombocytopenia (10.0%). Fondaparinux was generally well tolerated. Adverse events included bleeding events (n = 5), abortion (n = 2), premature births (n = 2), stillbirth (n = 1), arrested labors (n = 2), injection site erythema (n = 4) and unspecified drug hypersensitivity (n = 6). No VTE events or increased liver enzymes occurred during treatment. In this retrospective study, fondaparinux was effective and well tolerated. Trial registration: ClinicalTrials.gov NCT01004939.